Does advanced footwear technology improve track and road racing performance? An explorative analysis based on the 100 best yearly performances in the world between 2010 and 2022 - Willwacher, S.; Mai, P.; Helwig, J.; Hipper, M.; Utku, B.; Robbin, J. (Sports Medicine - Open, 2024)
Advanced footwear technology (AFT) is currently being debated in sports. There is a direct evidence that distance running in AFT improves running economy. In addition, there is indirect evidence from competition performance for improved running performance from using AFTs in middle- and long-distance running and sprinting events. However, the extent to which world-class performance is affected across the full range of track and road racing events between genders has not been systematically analyzed. This study examined publicly available performance datasets of annual best track and road performances for evidence of potential systematic performance effects following the introduction of AFT. The analysis was based on the 100 best performances per year for men and women in outdoor events from 2010 to 2022, provided by the world governing body of athletics (World Athletics). We found evidence of progressing improvements in track and road running performances after the introduction of AFT for road races in 2016 and AFT for track racing in 2019. This evidence is more pronounced for distances longer than 1500 m in women and longer than 5000 m in men. Women seem to benefit more from AFT in distance running events than men. For the sprint events (100 m to 400 m hurdles), the peak performance gains in 2021 and 2022 compared to the pre-AFT period ranged from 0.6 to 1.1% and from 0.4 to 0.7% for women and men, respectively. For middle-distance events (400 m to 3000 m steeplechase), peak performance gains ranged from 0.6 to 1.9% and from 0.6 to 0.7% for women and men, respectively. For distances from 5000 m to the marathon, performance gains ranged from 2.2% to 3.5% and 0.7% to 1.4% for women and men, respectively. While the observational study design limits causal inference, this study provides a database on potential systematic performance effects after introducing advanced shoes/spikes in track and road running events in world-class athletes. Further research is needed to examine the underlying mechanisms and, in particular, potential gender differences in the performance effects of AFT.